2005
DOI: 10.1007/s10549-004-6455-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of perductal paclitaxel exposure on the development of MNU-induced mammary carcinoma in female S–D rats

Abstract: Local administration of paclitaxel may be useful for treatment of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Tumor development was followed at weekly intervals. Tumors > 10 mm 3 and those that showed a progressive increase in size were scored. Intraductal administration of PLD significantly (P < 0.001, Table 2) protected animals against tumor formation Figure 1.…”
Section: Model I: Mnu-induced Rat Mammary Tumor Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor development was followed at weekly intervals. Tumors > 10 mm 3 and those that showed a progressive increase in size were scored. Intraductal administration of PLD significantly (P < 0.001, Table 2) protected animals against tumor formation Figure 1.…”
Section: Model I: Mnu-induced Rat Mammary Tumor Modelmentioning
confidence: 99%
“…SpragueDawley rats (n = 12) were administered MNU (50 mg/kg) to induce breast tumor development. Tumor treatment was initiated at an approximate size of 500 mm 3 . Tumors were either administered PLD (100 Ag) once per week for 2 weeks or received no treatment.…”
Section: Model I: Mnu-induced Rat Mammary Tumor Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Okugawa and colleagues showed that rats with N-methyl N'-nitrosourea (MNU)-induced breast tumors exhibited significant reduction in tumor burden and total number of mammary carcinomas when treated with intraductal paclitaxel (27). Similarly, Sukumar and colleagues have shown that intraductal administration of various anticancer drugs, such as pegylated liposomal doxorubicin (PLD), 4-hydroxytamoxifen carboplatin, methotrexate, nanoparticle albuminbound paclitaxel, and 5-fluorouracil was associated with a significant reduction in tumor formation or protected against tumor development in the MNU model, and also minimized the toxic effects of the drugs (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…For example, results of recent studies have shown that rats with N-methyl N′-nitrosourea-induced breast tumors exhibited significant reduction in tumor formation upon intraductal treatment with various anticancer agents, including paclitaxel, pegylated liposomal doxorubicin (PLD), 4-hydroxytamoxifen, carboplatin, methotrexate, nanoparticle albumin-bound paclitaxel and 5-fluorouracil, with minimal toxic effects. 2022 Similarly, human epidermal growth factor receptor 2/ neu transgenic mice, which spontaneously develop neu overex-pressing multifocal mammary adenocarcinoma beginning at approximately 4–5 months of age, exhibited higher levels of tumor regression and prevention of tumor development upon intraductal PLD treatment than mice that received intravenous PLD. 21 …”
Section: Introductionmentioning
confidence: 99%